Development of micro, small, and medium enterprises in Kutai beach tourism destinations, Central Tapanuli Regency - Sinta Veronika Hutabarat; Indra Setiawan Hutabarat; Yenni Sofiana Tambunan; Yusi Tri Utari Panggabean; Rahmadiah Hanum (Jurnal Mantik, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a role in economic improvement for regions and countries, more than that MSMEs can act as broad providers of employment, contribute to reducing unemployment, and bring welfare. This study aims to: 1) Know the condition and development of MSMEs, 2) Know the potential of MSMEs. 3) Finding effective strategies to develop MSMEs. This study uses a mixed research approach, namely by using quantitative data and qualitative data. Quantitative data in this study was obtained with the help of questionnaires to 140 respondents, consisting of 60 business actors and 80 tourists. Qualitative data were obtained with the help of interviews with the Banking and Regional Apparatus Organizations (OPD) at the locus of study. This study was conducted in Pandan District, Central Tapanuli Regency, North Sumatra Province. This study will be conducted from June 6 to August 29, 2023.